Novel Wide-Band Dielectric Imaging System Guided Lead Deployment for His Bundle Pacing: A Feasibility Study - Hua, Wei; Liu, Xi; Gu, Min; Niu, Hong-xia; Chen, Xuhua; Tang, Min; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2021)
Introduction: His bundle pacing (HBP) is the most widely used physiological pacing modality, but difficulties in locating the His bundle lead to high fluoroscopic exposure. An electroanatomical mapping (EAM) system can be an efficient tool to achieve HBP implantation with near-zero fluoroscopic visualization. Methods: In the study, 20 patients who had indications for pacemaker implantation were prospectively enrolled and underwent HBP implantation either with the conventional fluoroscopy approach (the standard group) or guided by a novel KODEX-EPD mapping system (the EAM-guided group). The success rate, procedural details, pacing parameters, and procedure-related complications were compared between the two groups. Results: In the study, 20 consecutive patients were randomized with 10 patients in each group. HBP was successfully achieved in nine patients in the standard group and nine patients in the EAM-guided group. The procedural time was similar between the EAM-guided group vs. the standard group (85.40 ± 22.34 vs. 86.50 ± 15.05 min, p = 0.90). In comparison with the standard group, the EAM-guided group had a significant shorter total fluoroscopic time (FT) (1.45 ± 0.58 vs. 12.36 ± 5.46 min, p < 0.01) and His lead fluoroscopic time (HL-FT) (0.84 ± 0.56 vs. 9.27 ± 5.44 min, p < 0.01), while lower total fluoroscopic dose (3.13 ± 1.24 vs. 25.38 ± 11.15 mGy, p < 0.01) and His lead fluoroscopic dose (1.85 ± 1.17 vs. 19.06 ± 11.03 mGy, p < 0.01). No significant differences were observed in paced QRS duration and pacing parameters between the two groups. During a 3-month follow-up, one patient had a capture threshold increased >1 V/1.0 ms in the standard group, while no other complications were recorded in either group. Conclusion: The KODEX-EPD system could facilitate HBP implantation with significantly reduced FT and dose without compromising the procedural time.